Improvement on the Design of a Palm Fruit Lifting Device for Truck - Ling, Martin; HJ. MOHD AZWIR BIN AZLAN; Shahrin Hisham Amirnordin; Ahmad Fu'ad Idris (Research Progress in Mechanical and Manufacturing Engineering, 2026)
The oil palm sector, particularly in Malaysia, is a vital contributor to the global supply; however, harvesting and loading fresh fruit bunches (FFBs) onto trucks is still a labor-intensive operation that causes serious musculoskeletal diseases in workers. This project overcomes the limitations of an earlier lifting device design done by Wan Sayyidil Athir, which was determined to be extremely heavy at 370.56 kg, with a lifting speed of 0.78 m/s that didn’t achieve the targeted speed at around 1 m/s, and was unsuitable for remote locations due to its reliance on a stable electrical supply. This study focuses on three key improvements: a lightweight design with a target weight under 250 kg, an engine-driven power system for plantation areas that are weak in electrical supply, and a flexible, foldable structure for easier storage and transport. The design process included the creation of 3D models, motion simulations, and detailed engineering drawings using SolidWorks software, following a modified George E. Dieter design method. The results of this project include an improved lifting device utilizing a power transmission system with an engine and gearbox to achieve a lifting speed of 0.96 m/s, meeting user expectations for efficiency. This project successfully achieves its objectives by enhancing the device’s field-adaptability and providing a more portable solution for actual plantation settings.